6. \( \begin{aligned} 4 x-3 y & =5 \\ 6 x+2 y & =14\end{aligned} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve the system of equations, you can use either substitution or elimination. Here, I'll use the elimination method. First, we can multiply the first equation by 2 to align the \(y\) coefficients. This gives us: \[ \begin{aligned} 8x - 6y & = 10 \quad (1) \\ 6x + 2y & = 14 \quad (2) \end{aligned} \] Now, multiply (2) by 3 to match the coefficients of \(y\): \[ \begin{aligned} 6x + 2y & = 14 \quad \text{multiply by 3 gives} \\ 18x + 6y & = 42 \quad (3) \end{aligned} \] Next, now that we have the same coefficient of \(y\) in both equations: \[ \begin{aligned} 8x - 6y & = 10 \quad (1) \\ 18x + 6y & = 42 \quad (3) \end{aligned} \] Add (1) and (3) to eliminate \(y\): \[ 26x = 52 \] \[ x = 2 \] Substitute \(x = 2\) back into one of the original equations to find \(y\). Using the first equation: \[ 4(2) - 3y = 5 \] \[ 8 - 3y = 5 \] \[ -3y = -3 \implies y = 1 \] Thus, the solution to the system of equations is \( (2, 1) \).